PENGARUH KEBIJAKAN DIVIDEN DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI PEMODERASI - Kevin .; Thio Anastasia Petronila (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
The management always provides prosperity for investors or shareholders through the value creation of the firm. The policy of dividend and company growth was considered by investors or shareholders in making investment decisions. This research aims to analyze the impact of the policy of dividend and growth opportunity on the value of a firm. Also, to analyze the effect of institutional ownership in moderating approach of dividend and growth opportunity in value of a firm. The research population was the Miscellaneous Industry sub-sector of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2016-2019. According to purposive sampling and outlier data, of the 27 companies, there are 13 companies with 46 units of observations units as a sample in this research. The data were obtained from annual reports that have been audited and published in IDX. The research results show that the dividend policy has an impact on the value of the firm provided by PBV, but growth opportunity is vice versa. Institutional ownership moderates the relationship between a policy of dividend and the value of a firm, while institutional ownership does not moderate the relationship between growth opportunity and the value of the firm